Optimization of Theophylline Tablet Formula Using CoProcessed Excipients of Lactose and Avicel - Hayatus Sa`adah; Achmad Fudholi (Indonesian Journal of Pharmacy, 2011)
Tablet  excipients  in  direct  compression  should  have  good  flowability  and compactibility.  Improvement  of  excipients  properties  may  be  obtained  by  coprocessing. Co-processing is defined as combining two or more excipients by an appropriate  process.  Co-processed  excipients  of  lactose  and  avicel,  which  were fabricated  by  spray  drying  technique,  would  be  used  as  filler-binder  in theophylline  tablet  formulation.  The co-processed excipients were evaluated for their  physical  properties,  i.e;  particle  size  distribution,  average  diameter, density,  flowability,  compactibility  and  water  absorption.  Simplex  lattice  design was  used  for  optimizing  flowability,  compactibility  and  water  absorption  of  coprocessed  excipients.  The  results  showed  that  proportion  of  lactose  and  avicel with  optimum  physical  properties  was  determined  by  the  ratio  1:1  with  a response of flowability was 8.79 ± 0.02 seconds, compactibility was 5.61 ± 0.08 kg and water absorption was 61.30 ± 0.40 mg/min. Superimposed contour plot of  theophylline  tablet  formulation  using  co-processed  excipients  as  filler-binder by  factorial  design  was  determined  by  the  optimum  proportion  of  magnesium stearate  and  eksplotab  (1:3.74)  with  the  response  of  hardness  was  5.54  ± 0.042  kg,  friability  was  0.303 ±  0.015%, disintegration  time was  1.83 ±  0.115 minutes and DE20was 85.66 ± 0.35%.Key words: theophylline tablets; co-processed excipients; lactose; avicel